The supply of democracy explaining voluntary democratic transition - Thomas Apolte (Westfälische Wilhelms-Universität Münster, Centrum für Interdisziplinäre Wirtschaftsforschung (CIW), 2013)
The theory presented in this paper explains democratic transitions on the basis of rentmaximizing political leaders that aim at improving the credibility of post-constitutional policy making by way of introducing a decentralized democratic politico-institutional structure. They face an incentive for doing so if such a structure is a precondition for Schumpeterian growth processes, as this raises opportunities for trading a part of the political leader's power potential against future political rents stemming from an enhanced macroeconomic income base. While a differentiated and decentralized politico-institutional setting to unfold its desired economic effects requires the political leaders to effectively respect the independence of decentralized political agencies, announcements to do so may not be credible. Hence, the conditions under which credibility can be reached are analyzed. As far as political leaders have an incentive to formally introduce democratic institutions and, additionally, as far as they are able to credibly commit to the effective independence of decentralized governmental agencies, they can be expected to voluntarily supply democracy.
Keywords: 330; Constitutional Economics; Political Economy of Democratization; Self-Sustaining Democracy